Sosialisasi Komunikasi Efektif Kepada Kader Posyandu Desa Pandean: Sosialisasi Komunikasi Efektif Kepada Kader Posyandu Desa Pandean - Saputro, Eko Wahyu; Rahmat Wisudawanto (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2025)
This community service is a service activity regarding the socialization of the importance of effective communication in serving the basic health of rural communities. Posyandu cadres play an important role in health services, where what they convey will be accepted and considered as the right thing by the community. In conveying information, especially about information that has a major impact on human resources and the quality of health for the community, accuracy, understanding, and the ability to convey good information are needed to avoid miscommunication of information. This service aims to remind, invite, and educate posyandu cadres to be able to carry out communication activities effectively. Community service in the form of socialization of effective communication to posyandu cadres located on Pandean Village received a good response and results where posyandu cadres could understand the material and increase the motivation of posyandu cadres to provide better services.